Methodology Adopted by NGOs for Farm Women Development - K. Atchuta Raju; M. Sudha Rani; M. C. Obaiah; G.S. Roy; T. Sarah Kamala (Journal of Agricultural Extension Management, 2025)
Indian women who are handicapped by social customs, traditions and social evils need special attention so that,-they can play their full and proper role in national life. To improve the status of women, it becomes essential to make them understand their role in the process of their development and consequently of their society. Non-Governmental Organisations are undertaking number of programmes to promote women welfare and development. The farming community in India comprises three groups; namely male farmers, women farmers and young farmers. It has been estimated that women farmers perform more than sixty per cent of farm activities. The majority of rural women in India, as we ll as in other developing countries, actively participate in farm related operations, besides fulfilling their responsibilities as home makers. The role of voluntary organisations revealed that no government department can be free from the out moded rules in the foreseeable future and that only autonomous bodies such as voluntary agencies committed to rural development would be in a position to make the responsibility not only for production programmes but also for eradication of hunger. Hence, the present endeavour has been designed to study the methodology adopted by NGO’s for farm women development